2016
DOI: 10.5114/pg.2016.57941
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of celiac disease in patients with irritable bowel syndrome and its subtypes

Abstract: IntroductionIrritable bowel syndrome (IBS) and celiac disease (CD) share some gastrointestinal symptoms. Celiac disease should be considered in a differential diagnosis of IBS.AimTo estimate the prevalence of predispositions to CD in patients with IBS and its subtypes.Material and methodsThe study included 48 patients (40 women, 8 men; average age: 41.1 ±14.6 years) with IBS, and a control group: 20 healthy volunteers. All participants completed a questionnaire on their current gastrointestinal symptoms and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…Studies with transgenic mice sensitised by gluten demonstrated that human leucocyte antigen DQ8 (HLA-DQ8) show an altered barrier function and enhanced muscle contractility—mechanisms previously observed in IBS patients [ 124 ]. Recently, it was shown that up to 50% of IBS patients have the genetic factors (HLA-DQ2/DQ8) predisposing to gluten sensitivity [ 125 ], which was in line with the findings of Catassi et al in a review of the effectiveness of gluten-free diet in IBS, which identified an overall positive response [ 122 ]. However, a recent RCT involving a gluten challenge showed that 49% of non-celiac gluten-sensitive individuals paradoxically developed symptoms after a gluten-free diet [ 126 ].…”
Section: Diet Bacteria and Ibssupporting
confidence: 66%
“…Studies with transgenic mice sensitised by gluten demonstrated that human leucocyte antigen DQ8 (HLA-DQ8) show an altered barrier function and enhanced muscle contractility—mechanisms previously observed in IBS patients [ 124 ]. Recently, it was shown that up to 50% of IBS patients have the genetic factors (HLA-DQ2/DQ8) predisposing to gluten sensitivity [ 125 ], which was in line with the findings of Catassi et al in a review of the effectiveness of gluten-free diet in IBS, which identified an overall positive response [ 122 ]. However, a recent RCT involving a gluten challenge showed that 49% of non-celiac gluten-sensitive individuals paradoxically developed symptoms after a gluten-free diet [ 126 ].…”
Section: Diet Bacteria and Ibssupporting
confidence: 66%
“…Due to this mimicry, the CD is often misdiagnosed as IBS and increases its morbidity. 20 The mean age in our study was 28.40 + 5.06. Out of 210 patients enrolled, 53.8% were males and 46.2% were females.…”
Section: Discussionmentioning
confidence: 62%
“…Evaluating data from nearby countries, in Poland CD prevalence among IBS-D patients was high: 7% (serological and histological CD detection) [25] or 12.5% among IBS patients regardless of the subtype (serological and genetical CD detection) [26]. At the same time, low prevalence (0.3% and 0.4%) of the biopsy-proven CD was detected in IBS patients from a high CD prevalence country Norway, all of whom fulfilled the Rome III criteria for IBS-D [5,6].…”
Section: Discussionmentioning
confidence: 99%